Artificial intelligence in providing the first and second signal systems with polysensory information for precise coordination of volleyball players actions - Khaupshev, M. K.; Bazhev, A. Z.; Khezhev, A. A.; Bazhev, A. A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to justify the use of artificial intelligence in managing the process of precise coordination of the actions of volleyball players.